Sulfide:quinone oxidoreductase alleviates ferroptosis in acute kidney injury via ameliorating mitochondrial dysfunction of renal tubular epithelial cells - Fangfang Cai; Dangran Li; Yawen Xie; Xiaoyang Wang; Hailin Ma; Huangru Xu; Jian Cheng; Hongqin Zhuang; Zi-Chun Hua (Redox Biology, 2024)
Ferroptosis is iron-dependent and regulates necrosis caused by lipid peroxidation and mitochondrial damage. Recent evidence has revealed an emerging role for ferroptosis in the pathophysiology of acute kidney injury (AKI). Sulfide:quinone oxidoreductase (SQOR) is a mitochondrial inner membrane protein highly expressed in the renal cortex. However, the effects of SQOR on ferroptosis and AKI have not been elucidated. In this study, we evaluated the effects of SQOR in several AKI models. We observed a rapid decrease in SQOR expression after cisplatin stimulation in both in vivo and in vitro models. SQOR-deletion mice exhibit exacerbated kidney impairment and ferroptosis in renal tubular epithelial cells following cisplatin injury. Additionally, our results showed that the overexpression of SQOR or ADT-OH (the slow-releasing H2S donor) preserved renal function in the three AKI mouse models. These effects were evidenced by lower levels of serum creatinine (SCr), blood urea nitrogen (BUN), renal neutrophil gelatinase-associated lipocalin (NGAL), and kidney injury molecule 1 (KIM-1). Importantly, SQOR knockout significantly aggravates cisplatin-induced ferroptosis by promoting mitochondrial dysfunction in renal tubular epithelial cells (RTECs). Moreover, online database analysis combined with our study revealed that SYVN1, an upregulated E3 ubiquitin ligase, may mediate the ubiquitin-mediated degradation of SQOR in AKI. Consequently, our results suggest that SYVN1-mediated ubiquitination degradation of SQOR may induce mitochondrial dysfunction in RTECs, exacerbating ferroptosis and thereby promoting the occurrence and development of AKI. Hence, targeting the SYVN1-SQOR axis could be a potential therapeutic strategy for AKI treatment.